Pengaruh Penggunaan Media Sosial terhadap Keterampilan Komunikasi Interpersonal Siswa SMA Swasta Kartika 1-4 Pematangsiantar - Harahap, Rika Rahmadhani (Medan Resource Center, 2022)
This study aims to analyze the impact of social media usage on the interpersonal communication skills of high school students. The background of this research is the increasing use of social media among teenagers and its potential impact on various aspects of interpersonal communication. The research method employed is qualitative, with a survey approach. Data analysis was conducted using linear regression techniques to examine the relationship between the independent variable (the intensity of social media use) and the dependent variable (interpersonal communication skills). The results of the study show a significant influence of social media use on students' interpersonal communication skills. Students who use social media with high intensity tend to have better interpersonal communication skills compared to those who use social media with low intensity. Additionally, the type of social media platform used also affects communication skills. More interactive platforms, such as Instagram and WhatsApp, have a greater positive impact compared to other platforms like Facebook and Twitter.